Monitoring stress and recovery among u/20 rugby union players over a training season ? - Nel, T. (2012)
Stress and recovery plays an important role in the performance of semi-professional rugby players. Physiological and psychological markers have been established as reliable indicators of the recovery-stress state in athletes. Monitoring changes in the recovery-stress state enables the coaching staff to adapt training sessions to enhance performance. The aim of this study was to monitor changes in stress and recovery states among U-20 rugby union players during a training year. Relationships regarding monitoring variables and differences in stress and recovery between playing positions were examined. 55 Players between the ages of 18 and 20 were monitored for 27 weeks, over a training year. The training year was divided into 5 training phases: Developing phase (week 1 - 7), Transitional phase (week 8 - 11), Early Competition phase (week 12 - 17), Performance phase (week 18 - 24), and High Performance phase (week 25 - 27). Ratings of Perceived Exertion (RPE) for sessions were reported on a daily basis. The Heart-rate Interval Monitoring System (HIMS) test was run every week. The Stellenbosch Mood Scale (STEMS) and Self-Report questionnaires were completed on a weekly basis, and the Recovery-Stress Questionnaire (RESTQ-76-Sport) was completed once a month. Backline players physically recovered better and faster than the forwards throughout the training year, while the forwards exhibited better psychological coping methods. The backline players had significant higher scores for the Depression (p = 0.03), Anger (p = 0.009), and Confusion (p = 0.01) scales of the STEMS. The Total Mood Disturbance scores were also significantly higher (p = 0.03) for the backline players than the forwards during the Performance phase. The backline players experienced increased stress and decreased feelings of well-being during the competitive phases when compared to the forwards. The backline players had better physical recovery than the forwards after the high intensity and high volume Developing phase. Correlations were evident between the HIMS test and the RESTQ-76-Sport questionnaire. Additional correlations were found between training load, as well as training monotony and training strain, and scales of the RESTQ-76-Sport and STEMS questionnaires. Lack of psychological skills-training might also have resulted in the players not knowing how to properly handle stressful situations and how to regulate their stress and recovery states. The lack of an educational system regarding recovery strategies, and the reinforcement thereof, especially during the Developing phases might play a role in the later increased fatigue and injury rates among the players.